Quantum Sensing in a Physiological‐Like Cell Niche Using Fluorescent Nanodiamonds Embedded in Electrospun Polymer Nanofibers. Issue 22 (22nd April 2019) - Price, Joshua C.; Levett, Simon J.; Radu, Valentin; Simpson, David A.; Barcons, Aina Mogas; Adams, Christopher F.; Mather, Melissa L.
Abstract: Fluorescent nanodiamonds (fNDs) containing nitrogen vacancy (NV) centers are promising candidates for quantum sensing in biological environments. This work describes the fabrication and implementation of electrospun poly lactic‐ co ‐glycolic acid (PLGA) nanofibers embedded with fNDs for optical quantum sensing in an environment, which recapitulates the nanoscale architecture and topography of the cell niche. A protocol that produces uniformly dispersed fNDs within electrospun nanofibers is demonstrated and the resulting fibers are characterized using fluorescent microscopy and scanning electron microscopy (SEM). Optically detected magnetic resonance (ODMR) and longitudinal spin relaxometry results for fNDs and embedded fNDs are compared. A new approach for fast detection of time varying magnetic fields external to the fND embedded nanofibers is demonstrated. ODMR spectra are successfully acquired from a culture of live differentiated neural stem cells functioning as a connected neural network grown on fND embedded nanofibers. This work advances the current state of the art in quantum sensing by providing a versatile sensing platform that can be tailored to produce physiological‐like cell niches to replicate biologically relevant growth environments and fast measurement protocols for the detection of co‐ordinated endogenous signals from clinically relevant populations of electrically active neuronal circuits. Abstract : A quantum sensing platform that mimics the nanoscale architecture and topography of the cell niche is presented based on the incorporation of fluorescent nanodiamonds containing nitrogen vacancies in electrospun poly lactic‐ co ‐glycolic acid nanofibers. The sensing platform supports the establishment of electrically active neuronal networks and measurement protocols presented enable fast detection of optically detected magnetic resonance from live cells.